A sustentabilidade de sistemas produtivos de cacau (Theobroma cacao) e açaí (Euterpe oleracea) no bioma Amazônia - Machado, Richard Luan Silva (2024)
In addition to human actions involving the direct destruction of vegetation, the expan-sion of cocoa (Theobroma cacao) and açaí (Euterpe oleracea) agriculture in the Ama-zon biome requires a delicate balance to ensure economic production, environmental conservation, and social impacts minimum. The production of both crops has provoked intense debate among current production systems. In this sense, sustainability indica-tors were used to quantify the real impact of the production chain of these commodities. The system limits cover production from cradle to gate, using the functional unit of 1 hectare for each proposed system. The results of this study demonstrated that cocoa monoculture recorded the largest carbon footprint (1.35 tCO2eq), followed by cocoa and açaí agroforestry (1.20 tCO2eq), açaí monoculture (0.84 tCO2eq), and cocoa and açaí extractivism (0.25 tCO2eq). Carbon balance analysis revealed significant carbon capturing in almost all areas studied. The areas within Indigenous lands presented a balance of -1.6 tCO2eq, cocoa monoculture (-3.86 tCO2eq), açaí (-3.70 tCO2eq), agro-forestry systems (-3.81 tCO2eq) and extractivism (-4.17 tCO2eq), unlike the areas out-side Indigenous lands that presented a positive value (0.70 tCO2eq). Regarding profit-ability, the net profit was USD 6783.44/ha for açaí monoculture, USD 6059.42/ha for extractivism, USD 4505.55/ha for agroforestry and USD 3937.32/ha for cocoa mono-culture. In the social aspect, the most relevant negative impacts on cocoa and açaí production include child labor and gender discrimination, while the positive impacts are linked to the reduction of forced labor. Among the production systems, extractivism has proven to be an excellent choice for a balanced trade-off between production and forest conservation. In addition, the agroforestry system also stands out among the systems for local communities and global production. Thus, this research demonstrates that the simultaneous production of both crops, especially when integrated into an environmen-tally sustainable management plan, can be viable for production in the food chain.